The Analysis of Flouting Maxim in Raya and The Last Dragon Movie - Astini, Ni Wayan Siska; Candra, Komang Dian Puspita; Marantika , I Made Yogi (Journal of Language and Applied Linguistics, 2023)
This article aims to find out the types of flouting maxims in the Raya and The Last Dragon movie is. The researcher used the theory that proposed by Grice in his book (1975) to analyze the types of flouting maxims in Raya and The Last Dragon movie. The method that used in this research is descriptive qualitative research. Through the findings of the analysis, there were 17 data found. Those are: Flouting Maxim of Quantity 6 data (35%), Flouting Maxim of Quality 3 data (17% ) Flouting Maxim of Relevance and Flouting Maxim of Manner rarely appeared with same frequently 4 data (24%). From those forms, Flouting Maxim of Quantity has the highest occurrences used among others.